Long non-coding RNA PSMB8-AS1 regulates influenza virus replication. Issue 3 (4th March 2019) - More, Sunil; Zhu, Zhengyu; Lin, Kong; Huang, Chaoqun; Pushparaj, Samuel; Liang, Yurong; Sathiaseelan, Roshini; Yang, Xiaoyun; Liu, Lin
ABSTRACT: Long non-coding RNAs (lncRNAs) are a new arm of gene regulatory mechanism as discovered by sequencing techniques and follow-up functional studies. There are only few studies on lncRNAs as related to gene expression regulation and anti-viral activity during influenza virus infection. We sought to identify and characterize lncRNAs involved in influenza virus replication. Using RNA sequencing analysis, we found that 1, 912 lncRNAs were significantly changed in human lung epithelial A549 cells infected with influenza A/Puerto Rico/8/34. Gene ontology analysis on neighboring genes of these lncRNAs revealed that the genes involved in type I interferon signaling and cellular response were highly enriched. Seven selected up-regulated lncRNAs (AC015849.2, RP-1-7H24.1, PSMB8-AS1, CTD-2639E6.9, PSOR1C3, AC007283.5 and RP11-670E13.5) were verified by real-time PCR. These lncRNAs were also induced by other two influenza H1N1 virus strains (A/WSN/1933 and A/Oklahoma/3052/09) and interferon β1. Repression of PSMB8 antisense RNA 1 (PSMB8-AS1) using CRISPR interference reduced viral mRNA and protein levels as well as the release of progeny influenza virus particles. Our study suggests that lncRNA PSMB8-AS1 could be a new host factor target for developing antiviral therapy against influenza virus infection.